...oltre la malattia: Medicina narrativa per una terapia dell'anima - Luigi Ciaccia (AboutScience Srl, 2019)
Purpose: A patient diagnosed with chronic kidney disease (CKD) is forced to reorganise his/her entire lifestyle according to the rhythm of dialysis, a life-saving therapy that becomes a life-long sentence. Slowly, the clinic becomes a prison of pain and frustration, worsening the symptoms and affecting the medical staff as well. Thus, I decided to work on the doctor-patient relationship in order to guide those under therapy in finding a new perception of themselves "beyond the disease". Methods: In pursuing this goal, I adopted the methodology of narrative medicine, structured through three interviews: the first one on the disease; the second one on the past (i.e. emotions, fond memories, etc.); the third one on future projects. I also launched other weekly activities, such as sharing good news from the newspaper, watching movies, and organising outdoor activities. Results Throughout the project, I observed a significant improvement in the well-being of the patients, through a decrease in their stress levels and an increased response to therapy. Furthermore, I was able to establish a group dynamic among the patients as well as between them and the staff. Conclusions; At the end of the first year, the project was renewed, and its scope widened. We collected some photos and thoughts of the patients during our outdoor activities and published them in a book, which was given to the patients for Christmas, as the symbol of both the end of the first year and the start of another... beyond the disease. (narrative nephrology)